1999
DOI: 10.1037/0022-3514.76.1.129
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in social comparison: Development of a scale of social comparison orientation.

Abstract: Development and validation of a measure of individual differences in social comparison orientation (the Iowa-Netherlands Comparison Orientation Measure [INCOM]) are described. Assuming that the tendency toward social comparison is universal, the scale was constructed so as to be appropriate to and comparable in 2 cultures: American and Dutch. It was then administered to several thousand people in each country. Analyses of these data are presented indicating that the scale has good psychometric properties. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

42
1,263
7
50

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 1,235 publications
(1,362 citation statements)
references
References 71 publications
42
1,263
7
50
Order By: Relevance
“…That is, impressions about the fairness of an organization-level change procedure are not as useful for reducing uncertainty about people's abilities, opinions, and interpersonal relations as information conveyed by the treatment they receive from their supervisors. Consistent with this explanation, people high in social comparison orientation have been found to be particularly sensitive to others' behavior (Gibbons & Buunk, 1999). Our findings imply that as in other studies (e.g., Aquino et al, 1999) interactional justice perceptions may be stronger determinants of antisocial behaviors than are procedural or distributive justice perceptions.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…That is, impressions about the fairness of an organization-level change procedure are not as useful for reducing uncertainty about people's abilities, opinions, and interpersonal relations as information conveyed by the treatment they receive from their supervisors. Consistent with this explanation, people high in social comparison orientation have been found to be particularly sensitive to others' behavior (Gibbons & Buunk, 1999). Our findings imply that as in other studies (e.g., Aquino et al, 1999) interactional justice perceptions may be stronger determinants of antisocial behaviors than are procedural or distributive justice perceptions.…”
Section: Discussionsupporting
confidence: 88%
“…Supporting their argument, Gibbons and Buunk found that social comparison orientation was negatively correlated to selfesteem and positively related to social anxiety, neuroticism, and depression. Although social comparison orientation is positively related to this complex of negative cognitions and affect, studies show that social comparison orientation shares only a moderate correlation with neuroticism (Gibbons & Buunk, 1999). Moreover, social comparison orientation and neuroticism have independent effects on a variety of outcomes and distinct effects in response to comparison information (Buunk, Nauta, & Molleman, 2005;Buunk, Van der Zee, & Van Yperen, 2001; Van der Zee, Oldersma, Buunk, & Bos, 1998).…”
Section: Social Comparison Orientationmentioning
confidence: 99%
See 1 more Smart Citation
“…The Likert-type responses include a 5-point scale format ranging from 1 (strongly disagree) to 5 (strongly agree). Gibbons & Buunk, 1999;Piko, Luszczynska, Gibbons, & Teközel, 2005). The scale includes 11 items pertaining to how an individual compares himself or herself with others (e.g., "I always pay a lot of attention to how I do things compared with how others do things").…”
Section: Methodsmentioning
confidence: 99%
“…Similar to absolute outcomes, relative outcomes derived from social comparison processes can have dramatic impacts on personal well-being and interpersonal interactions [Bault et al, 2008;Gibbons and Buunk, 1999;Hughes and Beer, 2013;Muscatell et al, 2012;Olson et al, 2014;Rutledge et al, 2016;Zhen et al, 2016]. Evidence from a worldwide survey revealed that the impact of relative income was even larger than that of absolute income on selfreported happiness [Ball and Chernova, 2008].…”
Section: Introductionmentioning
confidence: 99%